Kesehatan Mental sebagai Variabel Moderasi Fasilitas Kerja terhadap Kepuasan Kerja - Siska Putri Belangi; Asmidar Asmidar (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to analyze the role of mental health as a moderation variable in the relationship between work facilities and employee job satisfaction. Adequate work facilities are generally thought to be able to increase job satisfaction, but these effects can vary depending on the individual's psychological condition, particularly mental health. This research is motivated by the importance of a holistic approach in human resource management, which includes both physical and psychological aspects of the work environment. The research method used was a quantitative approach with survey techniques to 150 respondents working in the public service sector in urban areas. The data collection instrument was in the form of a closed questionnaire with a Likert scale, and hypothesis testing was carried out through moderation regression analysis using the help of SPSS software. The results of the study show that work facilities have a positive and significant influence on employee job satisfaction. In addition, it was found that mental health played a significant role as a significant moderation variable in the relationship. This means that the influence of work facilities on job satisfaction becomes stronger or weaker depending on the level of mental health possessed by employees. These findings underscore the importance of organizations not only focusing on improving physical work facilities, but also paying attention to and managing employees' mental health as an integral part of strategies to improve well-being and work productivity. Interventions such as counseling programs, work-life balance, and stress management training need to be considered as part of the organization's policies. This research makes a theoretical contribution in enriching the understanding of the role of psychological variables in job satisfaction dynamics, as well as a practical contribution to management in designing a healthier and more productive work environment.